The Advantages and Disadvantages of Distance Learning for Students with Special Educational Needs and Disabilities During Covid-19 at University in UAE - Juma, Mariyam Salim (2020)
This study investigates the advantages and disadvantages of distance learning for SEND (students with special educational needs and disabilities) during COVID-19 crisis at the University in the United Arab Emirates (UAE). The study depends on the qualitative method using interview that depends on semi-structured interviews. Data was collected from SEND, teachers and special need education coordinator/ specialists’ perspectives. Overall the experience and thoughts were a mix up between positive and negative aspects of studying online from students with special educational needs and disabilities. I believe that the reason behind it, that remote learning has always been a debatable topic. Yet during COVID-19, the students have no choice to choose remote learning or traditional learning because the ministry of education in UAE forced all students to study remotely. In the long run, the outcomes of the remote learning experience depending on the type of disability, the readiness of the students, the acceptance to change and sometimes the type of course that students took. Findings show that most of the parties involve in the semi-structured interviews agreed that remote learning after categorizing it as a safety matter, it saves times and open a door to learn new technology skills. On the other hand, lack of communication interaction was the main disadvantages of remote learning as students feel lonely while attending classes, teachers can’t interact and can’t observe if the learning objective was met and specialists believe that students learn from other students sometimes and they missed this chance. Recommendations for the research was to keep training students and teachers on new strategies and new technology to be prepared for the future whether if any crisis occurred or for a job. Governments should study the case from a different angle to overcome all the challenges and include all learners in any policy and procedures. Limitation of the study was the limited access to higher education organizations. Also, the limited number of SEND involved as it is only from one university in the UAE. As well as depending on interviews only to follow the rule of no social interaction between people.